PENGARUH VARIASI TEKANAN SANDBLASTING TERHADAP LAPISAN HASIL POWDER COATING - Syamsuir; Yos Nofendri; Boy Martino; Naufan Erzha Sulistiono; Galih Panji Saputro; Ihsan Ady Prasetyo; Afdhal Fuaddy (Universitas Negeri Jakarta, 2022)
The problem of motor vehicles made from low carbon steel is corrosion. Almost all automotive components require coatings with the aim of protecting structures that are generally made of carbon steel from corrosion attacks. There are many techniques in painting, one of which is the powder coating technique, which is powder paint (powder) which can be loaded with static electricity to facilitate the process of painting using objects made of metal. Surface preparation needs to be done before the powder coating process is carried out. The most common preparation is by sandblasting, administration of phosphoric acid, or sandpaper. From the three preparations mentioned, the sandblasting method can be adjusted so that the pressure can get the desired roughness. So in this study, the effects of sandblasting pressure (4,5, and 6 bar) on the powder coating layer will be discussed. From the research that has been done, specimens with a pressure of 5 bar showed the highest abrasion resistance and contact angle.